2021
DOI: 10.3390/ijerph18126399
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on the Perception of Health and Treatment-Related Issues among Patients with Phenylketonuria in Poland—The Results of a National Online Survey

Abstract: There is agreement that the pandemic has affected the healthcare system and behaviour of patients. This study aims to identify problems encountered by patients with phenylketonuria (PKU) and their parents/caregivers during the six-week pandemic lockdown in Poland (15 March to 30 April 2020). To determine the factors that influenced health and treatment-related issues, as well as the respondents’ perception of the impact of the pandemic, study participants were asked to complete a non-validated online questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Nonetheless, even though stress is unavoidable, its effect can either be beneficial or harmful to an individual. Scholars have revealed that the harmful nature of stress affects two-thirds of the number of people who visit doctors (Drabick et al, 2021;Walkowiak et al, 2021;Zvada & Bhebhe, 2019). It has also been disclosed that Numerous studies have been carried out on occupational stress and job performance.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, even though stress is unavoidable, its effect can either be beneficial or harmful to an individual. Scholars have revealed that the harmful nature of stress affects two-thirds of the number of people who visit doctors (Drabick et al, 2021;Walkowiak et al, 2021;Zvada & Bhebhe, 2019). It has also been disclosed that Numerous studies have been carried out on occupational stress and job performance.…”
Section: Introductionmentioning
confidence: 99%
“…The non-validated questionnaire consisted of 31 questions, 27 of which were single choice, 2 multiple choice and 2 open-ended questions [ 8 ]. All questions referred to circumstances and pandemic-related events that may have directly or indirectly impacted our subjects’ health and therapy-related issues, as well as their perception of the consequences of the pandemic.…”
Section: Methodsmentioning
confidence: 99%
“…In a recently published national online survey on how PKU patients in Poland perceive health and therapy-related issues [ 8 ], we documented that 9.5% of our respondents failed to perform blood phenylalanine (Phe) tests throughout the examined six-week pandemic period (16 March–30 April 2020), with 21.3% reporting an increase in their blood Phe level as opposed to 15.3% who reported a decrease. Moreover, 26.1% of subjects found contacting their doctor or dietitian more difficult, while 39.3% perceived their access to the products necessary in their diet as restricted, but 63.4% were happy with the distance contact with their PKU specialist.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations